Population Pharmacokinetics of Upadacitinib Using the Immediate-Release and Extended-Release Formulations in Healthy Subjects and Subjects with Rheumatoid Arthritis: Analyses of Phase I–III Clinical Trials - Klünder, Ben; Mittapalli, Rajendar K.; Mohamed, Mohamed-Eslam F.; Friedel, Anna; Noertersheuser, Peter; Othman, Ahmed A. (Clinical pharmacokinetics, 2019)
Background and Objectives Upadacitinib is a selective Janus kinase (JAK) 1 inhibitor being developed as an orally administered treatment for patients with moderate to severe rheumatoid arthritis (RA) and other autoimmune disorders. These analyses characterized the population pharmacokinetics of upadacitinib across phase I–III clinical trials using data for immediate-release (IR) and extended-release (ER) formulations. Methods Pharmacokinetic data from 4170 subjects taking IR doses of 1–48 mg and ER doses of 7.5–30 mg across 12 studies spanning phase I–III clinical trials, with a total of 29,372 upadacitinib plasma concentrations, were analyzed using non-linear mixed-effects modeling. The model was evaluated using bootstrap analyses and visual predictive checks. Results A two-compartment model with first-order absorption with lag time for the IR formulation, mixed zero- and first-order absorption with lag time for the ER formulation, and linear elimination, adequately described upadacitinib plasma concentration–time profiles. Population estimates of upadacitinib apparent oral clearance and steady-state volume of distribution in healthy volunteers for the ER formulation were 53.7 L/h and 294 L, respectively. The relative bioavailability of the ER formulation compared with the IR formulation was estimated to be 76.2%. Statistically significant covariates were patient population (RA subjects vs. healthy subjects), creatinine clearance, and baseline bodyweight on apparent clearance (CL/F) and bodyweight on volume of distribution of the central compartment (Vc/F). The intersubject variability for upadacitinib CL/F and Vc/F were estimated to be 21% and 24%, respectively, in the phase I studies, and 37% and 53%, respectively, in the phase II/III studies. Upadacitinib area under the concentration–time curve (AUC) was estimated to be only 5% higher or lower for RA patients who were < 60 or > 100 kg, respectively, relative to subjects with a bodyweight of 60–100 kg. RA subjects with mild or moderate renal impairment had 13% and 26% higher AUC, respectively, compared with RA subjects with normal renal function. Sex, race, concomitant use of pH-modifying drugs, moderate cytochrome P450 3A inhibitors, or methotrexate use had no effect on upadacitinib exposure. Conclusions A robust population pharmacokinetic model was developed for upadacitinib using a large dataset from phase I–III clinical trials in healthy volunteers and subjects with RA. None of the identified covariates had a clinically meaningful effect on upadacitinib exposures. The model is appropriate to use for simulations and to evaluate the exposure–response relationship of upadacitinib.